Development of an L-Band SAR Microsatellite Antenna for Earth Observation - Katia Nagamine Urata; Josaphat Tetuko Sri Sumantyo; Cahya E. Santosa; Tor Viscor (Aerospace, 2018)
A compact synthetic aperture radar microsatellite antenna operating in the L-band is presented. To reduce size and weight of the small spaceborne SAR, we utilize a lightweight deployable parabolic mesh reflector and operate at low Earth orbital altitudes. The antenna is a wrap-rib center-fed parabolic reflector with dedicated receiving and transmitting feeds. Antenna requirements are: gain better than 30 dBic, center frequency of 1.275 GHz with bandwidth of 28 MHz and circular polarization with axial ratio better than 3 dB. This work describes the development of a compact Circularly Polarized SAR L-band antenna system and the design considerations suitable for small spacecrafts. Simulation of the parabolic reflector and effects of different structural elements to the main radiation pattern were analyzed, which include ribs, struts, feed blockage, and mesh surface. A research model of the parabolic reflector was constructed, and the reflector surface verification was realized using two different approaches, a laser distance meter along ribs and the other using 3D scanning of the reflector surface. RMS errors wree 1.92 mm and 3.86 mm, respectively, both below required 4.55 mm of surface accuracy. Near-field antenna measurements of the deployable reflector mesh antenna was realized for final antenna validation, presenting good agreement with the simulation results. Future work comprises prototyping and testing of the full polarimetric feed assembly.